TURKISH TEXTBOOKS AND CHILD CHARACTERS - Yasin Mahmut YAKAR (Fırat University, 2019)
The way the child characters in the textbooks are presented is important for children to identify themselves and reveal the social structure the society aims. Therefore, in this study, we aimed to determine the characteristics of the children characters in fictional texts in Turkish textbooks. The reason for such a study is that the absence of a study on children's characters in Turkish textbooks in the literature and that Turkish textbooks are the means with which children are in contact throughout their learning process and that a study on child characters will reveal the type of generation being trained. In the study, where document analysis was used, two samples were selected from the 5th and 6th grade Turkish textbooks which were in effect in the academic year of 2017-2018 and 40 fictional texts in these samples were examined. The fictional texts were descriptively analyzed in the focus of "child" using NVIVO 11 program and the content analysis was performed on the new data set following descriptive analysis. Following the content analysis, the characteristics of the child characters were classified under two categories as "positive" and "negative". The results of the study suggest that child characters are depicted with more positive features than negative traits. In addition, the children's characters that are in the foreground with their moral characteristics are not presented with a discourse on wisdom and work; children were not blamed for their negative acts (either consciously or unconsciously) it was uncertain whether some of the children characters' behaviors were positive or negative.